The Routledge International Handbook for Children's Rights and Disability - Beckett, Angharad; Callus, Anne-Marie (Routledge International Handbooks, 2023)
This handbook provides authoritative and cutting-edge analyses of various aspects of the rights and lives of disabled children around the world. Taking the UN Convention on the Rights of Persons with Disabilities (CRPD) and the UN Convention of the Rights of the Child (CRC) as conceptual frameworks, this work appraises the current state of affairs concerning the rights of disabled children across different stages of childhood, different life domains and different sociocultural contexts. Divided into four sections • Legislation and Policy • Children's Voice • The Life Course in Childhood • Life Domains in Childhood and comprising 37 newly-commissioned chapters featuring analyses of UN documents and case-studies from Australia, Brazil, Ethiopia, Hong Kong, Italy, the Netherlands, Norway, Papua New Guinea, Serbia, South Africa, Spain, Sweden, the United Kingdom, the United States and Vanuatu, its multidisciplinary approach reflects the complexities of the lives of disabled children and the multifarious nature of the strategies needed to ensure that their rights are upheld.